Clinical Effects of PET-CT Before Definite Concurrent Chemoradiotherapy in Patients With Unresectable Stage IIIA–IIIB Squamous Cell Carcinoma of the Lungs. (10th August 2022) - Lin, Wei-Chun; Chen, Wang-Ming; Chen, Mingchih; Shia, Ben-Chang; Wu, Szu-Yuan
Abstract : Purpose: No large-scale, retrospective cohort study with a long-term follow-up time has yet evaluated the effects of preoperative 18 F-FDG PET-CT on survival in patients with unresectable stages IIIA–IIIB squamous cell lung carcinoma (SqCLC) who received definite concurrent chemoradiotherapy (CCRT). Methods: We included patients with unresectable stages IIIA–IIIB SqCLC receiving definite CCRT and categorized them into 2 groups. The case group comprised patients who underwent pre-CCRT 18 F-FDG PET-CT, and the comparison group comprised patients who did not receive pre-CCRT 18 F-FDG PET-CT; the groups were matched at a ratio of 1:1. Results: The matching process yielded a final cohort of 4042 eligible patients (2021 and 2021 in the case and comparison groups, respectively). Multivariable Cox regression analyses revealed a positive correlation between patients with unresectable stages IIIA–IIIB SqCLC receiving definite CCRT and all-cause death in the pre-CCRT 18 F-FDG PET-CT (adjusted hazard ratio, 0.85; 95% confidence interval, 0.80–0.91; P < 0.0001). Conclusion: Pre-CCRT 18 F-FDG PET-CT was associated with more favorable survival in both patients with unresectable clinical stage IIIA and those with stage IIIB receiving definite CCRT.